Optimized Information Hiding using Discrete Wavelet Transform and Genetic Algorithm - Umamaheswari, G; Sumathi, C.P (International Journal of Computer Sciences and Engineering, 2025)
With rapid advances in the field of communication and information sharing, Steganography – the art of secret communication has gained much attention in recent years. Communicating sensitive information through media like text, sound image and video without being noticed by intruder has become a challenge. Steganography deals with the development of efficient algorithms by a combination of variety of techniques to achieve imperceptibility. This article analyzes the effect of using the Discrete Wavelet Transform for hiding secret data and optimizing it using the genetic algorithm to achieve better results.